The relationship between maternal chronic diseases and the risk of stillbirth (Latakia University Journal -Medical Sciences Series, 2021)
Background: Stillbirth is one of the most distressing events for the parents as well as the obstetrician. It is a sensitive indicator of the mother's care before and during childbirth and is associated with many risk factors. Therefore, in this paper, we studied the relationship between maternal chronic diseases and several other factors with stillbirth.Objective: The main objective is to study the relationship between maternal chronic diseases and the risk of stillbirth, secondary objectives are to study the relationship between stillbirth and mother age ,BMI, smoking and number of births.Patients and methods: Study type: case control. It included 20 patients with a gestational age of >22 weeks with a diagnosis of intrauterine fetal death, and 140 patients with a gestational age of >22 weeks who gave birth with a live fetus. A detailed medical history was taken for each patient, vital signs were measured, and general analyzes were performed. Ultrasound examination was performed to confirm intrauterine fetal death. We divided the patients into groups according to age and body mass index.Results: We found that chronic hypertension increases the risk of stillbirth (AOR=2.4) with a p-value=0.01, and the presence of chronic diabetes increases the risk of stillbirth (AOR=1.8) with a p-value=0.04. Also, asthma increases the risk of stillbirth (AOR=7.6) with p-value=0.002, the risk also increases with age. We found that primiparous women increase the risk of stillbirth with an odds of about two times with a p-value=0.04, and smoking increases the risk of stillbirth (AOR=3.5) with a p-value=0.008, we found that the risk of stillbirth increases with the increase in the body mass index (BMI), with statistically significant differences, and high gestational hypertension increases the risk of stillbirth (AOR=5.07) with a p-value=0.03, and finally we found that the presence of gestational diabetes increases the risk of stillbirth (AOR=7.6) with a p-value=0.002.Conclusion: Maternal chronic diseases, especially gestational diabetes, asthma and gestational hypertension, in addition to other factors (smoking, obesity, Mother's age ≥ 40 years and nulliparity) are risk factors associated with stillbirth and have significant statistical significance. Appropriate interventions must be found in these cases to prevent the occurrence of stillbirth.